Intestinal Stem Cells and Immune Cell Relationships: Potential Therapeutic Targets for Inflammatory Bowel Diseases - Hou, Qihang; Huang, Jingxi; Ayansola, Hammed; Masatoshi, Hori; Zhang, Bingkun (Frontiers in Immunology, 2021)
The mammalian intestine is the largest immune organ that contains the intestinal stem cells (ISC), differentiated epithelial cells (enterocytes, Paneth cells, goblet cells, tuft cells, etc.), and gut resident-immune cells (T cells, B cells, dendritic cells, innate lymphoid cell, etc.). Inflammatory bowel disease (IBD) – a chronic inflammatory disease that is characterized by mucosa damage and inflammation threatens the integrity of the intestine. The continuous renewal and repair of intestinal mucosal epithelium after injury depend on ISCs. Inflamed mucosa healing could be a new target for the improvement of clinical symptoms, disease recurrence, and resection-free survival in IBD treated patients. The knowledge about the connections between ISC and immune cells is expanding with the development of in vitro intestinal organoid culture and single-cell RNA sequencing technology. Recent findings implicate that immune cells such as T cells, ILCs, dendritic cells, and macrophages and cytokines secreted by these cells are critical in the regeneration of ISCs and intestinal epithelium. Transplantation of ISC to the inflamed mucosa may be a new therapeutic approach to reconstruct the epithelial barrier in IBD. Considering the links between ISC and immune cells, we predict that the integration of biological agents and ISC transplantation will revolutionize the future therapy of IBD patients.